His or para-His pacing preserves left ventricular function in atrioventricular block: a double-blind, randomized, crossover study. Issue 8 (7th February 2014) - Kronborg, Mads B.; Mortensen, Peter T.; Poulsen, Steen H.; Gerdes, Jens C.; Jensen, Henrik K.; Nielsen, Jens C.
Abstract : Aims: To compare left ventricular function after a long-term His or para-His pacing (HP) and right ventricular septal pacing (RVSP) in patients with atrioventricular block (AVB). Methods and results: We included consecutive patients with AVB, a narrow QRS < 120 ms, and a preserved left ventricular ejection fraction (LVEF) >0.40, in a prospective, randomized, double-blinded, crossover design. All patients were treated with 12 months HP and 12 months RVSP. A total of 38 patients [mean age, 67 ± 10 years; 30 (79%) men] were included. The primary endpoint was LVEF, which was significantly lower after a 12 months RVSP (0.50 ± 0.11) than after 12 months of HP (0.55 ± 0.10), P = 0.005. We measured the difference in time-to-peak systolic velocity between opposite basal segments in the apical views by using tissue Doppler imaging. In the four-chamber view, the difference was 58 (±7) ms after RVSP and 49 (±7) ms after HP, P = 0.27; in the two-chamber view, the difference was 45 (±5) ms after RVSP and 31 ±(4) ms after HP, P = 0.02, and in the apical long-axis view, the difference was 63 (±6) after RVSP and 44 (±7) after HP, P = 0.03. There was no difference in New York Heart Association class, 6-min hall walk test, quality-of-life assessments, or device-related complications. The mean threshold was significantly higher in HP leads than in RVSP leads. Conclusion: His or para-His pacing preserves LVEF and mechanical synchrony as compared with RVSP after 12 months pacing in patients with AVB, narrow QRS, and LVEF > 0.40.